PENGARUH KOMITMEN ORGANISASI, PEMBERIAN REWARD, TINGKAT KESERIUSAN KECURANGAN DAN PERSONAL COST OF REPORTING TERHADAP NIAT UNTUK MELAKUKAN WHISTLEBLOWING (Studi Empiris Pada OPD Di Kota Dumai) - Refina, Luqfia; M, Rasul; Supriono, Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study was aimed to examine the effect of organizational commitment, rewarding, the fercy level of fraud and personal cost of reporting to whistleblowing intention. Sample of this study is head of organizational regional device, head of subfinance, and treasurer who working in the Regional Device Organization Dumai city at 2020. The sampling method is used purposive sampling methode with total 102 respondents and the population 34 Regional Device Organization who used in this study. The data source used in the study was the primary data. Analysis of data is carried out using multiple regression analysis with the program of SPSS version 25.0 windows. The result proved that: (1) organizational commitment had a effect to Whistleblowing Intention. (2) rewarding had a effect to Whistleblowing Intention. (3) the fercy level of fraud had effect to Whistleblowing Intention. (4) personal cost of reporting had a effect to Whistleblowing Intention.Keyword : Organizational Commitment, Rewarding, The Fercy Level of Fraud and Personal Cost of Reporting, Whistleblowing Intention